A critical Analysis of Female characters in the Fiction of Begum Abdul Qadir - Ahsan, Samia (sourcecoder, 2023)
There was an aspect of romanticism which was very popular in Europe and especially in England during the romantic movement, but its tradition was not present in Urdu fiction. These were mysterious stories based on mystery, fear and terror. Mrs. Abdul Qadir introduced this style of story in Urdu. This attitude made her stand apart from the fiction writers of her time.In the stories of Mrs.Abdul Qadir, there is a deep influence of old legendry stories and mythology, but this influence is limited to the environment or events. As far as her characters are concerned, they are often simple and ordinary people, especially their female characters. In them we see the traditional woman of India. These characters belong to our own world but the events around them make them special and mysterious. Although Mrs. Abdul Qadir’s woman is usually a housewife, but she is not a timid and scared woman. Instead, she is strong, fearless and brave. Thus, the woman in her stories is oppressed but not passive. She fights against the odds and plays a possitive role in the life.